2006
DOI: 10.1159/000095523
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin-Like Growth Factor Binding Proteins

Abstract: Insulin-like growth factors (IGFs) are fundamental cell regulators with an evolutionary conserved role synchronising tissue growth, development and function according to metabolic conditions. Although structurally very similar to insulin, the IGFs act in a very different way as cell regulators. Whereas insulin is stored in a specific gland and released when needed, the IGFs are stored outside of cells with soluble binding proteins. A very complex system of six IGF binding proteins, each of which exists in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 87 publications
1
111
0
2
Order By: Relevance
“…However, serum IGFBP-2 levels are not indicative of an increased cancer risk because in these tumors, serum IGFBP-2 levels are generally normal before the diagnosis of cancer (12,30). Clinical data are paralleled by many in vitro studies, also showing IGFBP-2 overexpression in various different cancer cell lines (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, serum IGFBP-2 levels are not indicative of an increased cancer risk because in these tumors, serum IGFBP-2 levels are generally normal before the diagnosis of cancer (12,30). Clinical data are paralleled by many in vitro studies, also showing IGFBP-2 overexpression in various different cancer cell lines (31).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-1 is synthesized in the liver, where its expression is under the control of insulin which suppresses its production (74). It has also been suggested that GH directly regulates IGFBP-1 secretion (75).…”
Section: Regulation Of Gh Secretionmentioning
confidence: 99%
“…A possible mechanism linking disturbed sleep to metabolic disturbances, which has not yet been investigated, may be insulin-like growth factor-binding proteins (IGFBPs), proteins in the circulation that bind IGFs (IGF1 and IGF2) and determine the bioavailability of these factors, as well as having direct effects themselves (4). IGFBP1 secretion in humans is mainly regulated at transcriptional level by insulin (5) and also by other counterregulatory hormones like glucocorticoids (6) and growth hormone (GH).…”
Section: Introductionmentioning
confidence: 99%